Pengaruh Media Sosial, Perilaku Pembelian Impulsif, Kepercayaan Financial Technology dan Literasi Keuangan Terhadap Minat Penggunaan Shopee Paylater - Hutari Adeningsih; Said Said; Imam Tri Wibowo (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2026)
This study analyzes the influence of Social Media, Impulsive Buying Behavior, Financial Technology Trust, and Financial Literacy on the Interest in Using Shopee PayLater among Generation Z youth in Jombang Village, South Tangerang. Out of a population of 6,618 teenagers, a sample of 150 respondents was selected using Purposive Sampling, exceeding the initial Slovin formula requirement of 99 participants to ensure higher data reliability. The research adopts a quantitative approach with multiple linear regression analysis processed via SPSS version 25. Data collection integrated primary sources from structured questionnaires with secondary data from comprehensive literature reviews. The results demonstrate that Impulsive Buying Behavior and Financial Technology Trust significantly and positively affect Shopee PayLater usage interest. Conversely, Social Media and Financial Literacy do not show a significant positive impact to Shopee PayLater usage interest. These findings provide critical insights into the digital consumption patterns and financial decision-making behaviors of the modern Indonesian youth demographic.